2020
DOI: 10.3390/s20174968
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Anthropomorphic Phantom of the Axillary Region for Microwave Imaging Assessment

Abstract: We produced an anatomically and dielectrically realistic phantom of the axillary region to enable the experimental assessment of Axillary Lymph Node (ALN) imaging using microwave imaging technology. We segmented a thoracic Computed Tomography (CT) scan and created a computer-aided designed file containing the anatomical configuration of the axillary region. The phantom comprises five 3D-printed parts representing the main tissues of interest of the axillary region for the purpose of microwave imaging: fat, mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…As defined in the framework of the EMERALD project, the manufacturing process used to build up accurate ultra-wideband (UWB) phantoms has to be easily reproducible by an electrical engineer in a non-specific environment without extreme precautions, and to some extent at low cost. The specificity of the GeePs-L2S breast phantom and those suggested in our previous and current works on the head [ 19 , 32 ], breast [ 13 , 33 ], and thorax [ 34 , 35 ] phantoms, has been confirmed by the work of [ 14 , 15 , 16 , 17 , 18 ] and [ 36 , 37 , 38 , 39 ]. These phantoms composed of several 3D printed cavities are filled up with liquid mixtures made for example of Triton X-100 (TX-100, a non-ionic surfactant) and salt water, the concentrations are numerically adjusted so that the dielectric properties are close to the reference values over a wide frequency range.…”
Section: Methodssupporting
confidence: 76%
“…As defined in the framework of the EMERALD project, the manufacturing process used to build up accurate ultra-wideband (UWB) phantoms has to be easily reproducible by an electrical engineer in a non-specific environment without extreme precautions, and to some extent at low cost. The specificity of the GeePs-L2S breast phantom and those suggested in our previous and current works on the head [ 19 , 32 ], breast [ 13 , 33 ], and thorax [ 34 , 35 ] phantoms, has been confirmed by the work of [ 14 , 15 , 16 , 17 , 18 ] and [ 36 , 37 , 38 , 39 ]. These phantoms composed of several 3D printed cavities are filled up with liquid mixtures made for example of Triton X-100 (TX-100, a non-ionic surfactant) and salt water, the concentrations are numerically adjusted so that the dielectric properties are close to the reference values over a wide frequency range.…”
Section: Methodssupporting
confidence: 76%
“…We also used this methodology with a new objective: estimate dielectric properties of structures for which dielectric property information is still limited. As mentioned in Section 1, the assumptions behind our methodology limit the direct comparison of absolute dielectric property values with state‐of‐the‐art values measured with traditional methods, such as OECP 11,20 . Also, a comparison with the patients included in our study is not possible since no follow‐up of the patients was done.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the authors observed that the complex permittivity results extracted from the measurements on the external surfaces are dominated by the fat layer surrounding the ALNs at the time of excision, resulting in lower permittivity and conductivity. A large variability of dielectric property values was observed in all measurements (5–55 at 4 GHz 11,20 ). More recently, Yu et al 21 measured human intrathoracic LNs removed from lung cancer surgeries and verified metastasized LNs presented significantly higher dielectric properties than healthy LNs.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations